2011
DOI: 10.5114/wiitm.2011.25799
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conversion on outcome in laparoscopic colorectal cancer surgery.

Abstract: IntroductionLong-term results after laparoscopic surgery with conversion to open surgery for colorectal cancer are seldom published.AimThe study analysed the impact of conversion of laparoscopic surgery to open resection for colorectal cancer on short- and long-term results.Material and methodsThe prospectively collected data of 469 patients with colorectal cancer in the period from 1 January 2001 to 31 December 2006 were analysed. Short- and long-term results were compared.ResultsThe relative frequency of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Fifteen published studies containing data on conversion from laparoscopic to open colorectal cancer resection were identified (Table 1) [6,[8][9][10][14][15][16][17][18][19][20][21][22][23][24]. The initial search identified 3051 articles.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Fifteen published studies containing data on conversion from laparoscopic to open colorectal cancer resection were identified (Table 1) [6,[8][9][10][14][15][16][17][18][19][20][21][22][23][24]. The initial search identified 3051 articles.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…No difference was found in 30-day overall morbidity between COS and POS patients. Previously, two studies found a higher Overall (I−squared = 96.9%, p = 0.000) Rickert et al [34] Kang et al [32] Study Casillas et al [16] Gonzalez et al [18] Bouvet et al [25] Strohlein et al [15] Kaiser et al [26] Martinek et al [28] Slim et al [12] CLASICC trial [3] Begos et al [24] Hewett et al [27] Senagore et al [23] Pennincks et al [31] [3,12], but Slim et al [12] reported data from an early laparoscopic experience. Consistent with this result, there was no difference in the length of postoperative hospital stay.…”
Section: Discussionmentioning
confidence: 96%
“…Martinek et al [28] Unplanned laparotomy or wound enlargement above the necessity for specimen removal Mroczkowski et al [30] Procedures started in laparoscopic manner and ended in open manner…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations